The Communication Of Quantitative Information On Market Risk Using Graphics In The Annual Reports Of Banks And Securities Firms - Yaliya, Sofri; Casson, Peter (Asian Academy of Management (AAM), 1999)
The explosive growth of the derivatives markets1 and the highly publicised recent losses11 have created concerns among various parties about the possibility of increasing systemic risk. Systemic risk is the risk that a disruption ( in a firm, in a market segment, to a settlement system, etc.) causes widespread difficulties in other firms, in other market segments or to the financial system as a whole (see Shah 1977 for details).